Radiation risk assessment in professionals working in dental radiology area using buccal micronucleus cytome assay - Sadatullah, Syed; Dawasaz, Ali Azhar; Luqman, Master; Assiry, Ali A; Almeshari, Ahmed A; Togoo, Rafi Ahmad (The journal of contemporary dental practice, 2013)
The aim of this study was to assess the incidence of micronuclei (MN) in buccal mucosal cells of professionals working in radiology area to determine the risk of stochastic effects of radiation. All the professionals and students working in King Khalid University - College of Dentistry radiology area were included in the Risk Group (RG = 27). The Control Group (CG = 27) comprised of healthy individual matching the gender and age of the RG. Buccal mucosal scraping from all the 54 subjects of RG and CG were stained with Papanicolaou stain and observed under oil immersion lens (×100) for the presence of micronuclei (MN) in the exfoliated epithelial cells. There was no significant difference between the incidence of MN in RG and CG (p = >0.05) using t-test. Routine radiation protection protocol does minimize the risk of radiation induced cytotoxicity, however, screening of professionals should be carried out at regular intervals.